Comparable clinical and radiologic outcomes between an anatomic tunnel and a low tibial tunnel in remnant-preserving posterior cruciate ligament reconstruction - Yoon, Kyoung Ho; Kim, Jung Suk; Park, Jae Young; Park, Soo Yeon; Yeak, Raymond Dieu Kiat; Kim, Sang Gyun (SAGE Publications, 2021)
Background: There is currently no consensus on the optimal placement of the tibial tunnel for remnant-preserving posterior cruciate ligament (PCL) reconstruction. Purpose/hypothesis: The purpose of this study was to compare the clinical and radiologic outcomes of remnant-preserving PCL reconstruction using anatomic versus low tibial tunnels. We hypothesized that the outcomes of low tibial tunnel placement would be superior to those of anatomic tibial tunnel placement at the 2-year follow-up after remnant-preserving PCL reconstruction. Study design: Cohort study; Level of evidence, 3. Methods: We retrospectively reviewed the data for patients who underwent remnant-preserving PCL reconstruction between March 2011 and January 2018 with a minimum follow-up of 2 years (N = 63). On the basis of the tibial tunnel position on postoperative computed tomography, the patients were divided into those with anatomic placement (group A; n = 31) and those with low tunnel placement (group L; n = 32). Clinical scores (International Knee Documentation Committee subjective score, Lysholm score, and Tegner activity level), range of motion, complications, and stability test outcomes at follow-up were compared between the 2 groups. Graft signal on 1-year follow-up magnetic resonance imaging scans was compared between 22 patients in group A and 17 patients in group L. Results: There were no significant differences between groups regarding clinical scores or incidence of complications, no between-group differences in posterior drawer test results, and no side-to-side difference on Telos stress radiographs (5.2 ± 2.9 mm in group A vs 5.1 ± 2.8 mm in group L; P = .900). Postoperative 1-year follow-up magnetic resonance imaging scans showed excellent graft healing in both groups, with no significant difference between them. Conclusion: The clinical and radiologic outcomes and complication rate were comparable between anatomic tunnel placement and low tibial tunnel placement at 2-year follow-up after remnant-preserving PCL reconstruction. The findings of this study suggest that both tibial tunnel positions are clinically feasible for remnant-preserving PCL reconstruction.